2002
DOI: 10.1067/mva.2002.123095
|View full text |Cite
|
Sign up to set email alerts
|

Nature and significance of endoleaks and endotension: Summary of opinions expressed at an international conference

Abstract: The current endoleak classification system with some important modifications is adequate. Types I and II endoleak occur after 0 to 10% and 10% to 25% of EVARs, respectively. Many (30% to 100%) type II endoleaks will seal and have no detrimental effect, which never or rarely occurs with type I endoleaks. Not all endoleaks can be visualized with any technique, and increased pressure (endotension) can be transmitted through clot. Aneurysm pulsatility after EVAR correlates poorly with endoleaks and endotension. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
401
2
21

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(430 citation statements)
references
References 31 publications
6
401
2
21
Order By: Relevance
“…If the endoleak is accompanied by sac expansion, continuous intra-aneurysmal pressure increases the risk of AAA rupture (7,8). It was reported that most endoleaks, initially identified as a type II endoleak, spontaneously seal within several months (3,4). In our study, a type II endoleak occurred in 58.7% of patients immediately after EVAR, and decreased to 24.5% of patients at the last follow-up examination.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…If the endoleak is accompanied by sac expansion, continuous intra-aneurysmal pressure increases the risk of AAA rupture (7,8). It was reported that most endoleaks, initially identified as a type II endoleak, spontaneously seal within several months (3,4). In our study, a type II endoleak occurred in 58.7% of patients immediately after EVAR, and decreased to 24.5% of patients at the last follow-up examination.…”
Section: Discussionmentioning
confidence: 68%
“…A relationship between aneurysm size and endoleaks was previously reported (1,2). Most type II endoleaks spontaneously disappear over time, but 10%-25% persist for more than six months after EVAR (3)(4)(5)(6). Persistent endoleaks with aneurysmal sac expansion are at high risk of rupture because of the continuously elevated intra-aneurysmal pressure and require a second intervention, such as embolization (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Late rupture mesenteric artery (type IIa, 33%), lumbar arteries (type IIb, 64%) or other collateral blood vessels (accessory renal arteries, internal iliac arteries, gonadal, median sacral artery, 3%), into the perigraft space (aneurysm sac). Incidence of post-EVAR T2E has been identified in the range of 10.2-45%, [5][6][7][8] varying according to the sensitivity of the diagnostic method used. These leaks typically are found during routine ultrasound or computed tomography (CT) follow-up for EVAR.…”
Section: Type II Endoleak Following Endovascular Repair Of Infrarenalmentioning
confidence: 99%
“…To date, endoleaks have been classified into 5 different subtypes and types 1-5 are illustrated in (Greenhalgh and Powell 2008) Typically, endoleaks that are classified as type 3 or type 4 resolve spontaneously; however endoleaks classified as type 1 or type 2 often require surgical intervention (Greenhalgh and Powell 2008). Treatment options for type 5 remain controversial as surgeons remain divided on advocating immediate surgical repair versus a more conservative surveillance approach (Mennander et al 2005, Veith et al 2002. Migration of the stent-graft following the EVAR procedure is another complication associated with considerable postoperative morbidity.…”
Section: Complications Associated With Evarmentioning
confidence: 99%